Genetic analysis of the X chromosome in people with Lewy body dementia nominates new risk loci - Ece Bayram; Paolo Reho; Irene Litvan; International LBD Genomics Consortium; Jinhui Ding; J. Raphael Gibbs; Clifton L. Dalgard; Bryan J. Traynor; Sonja W. Scholz; Ruth Chia (npj Parkinson's Disease, 2024)
Abstract Sex influences the prevalence and symptoms of Lewy body dementia (LBD). However, genome-wide association studies typically focus on autosomal variants and exclude sex-specific risk factors. We addressed this gap by performing an X chromosome-wide association study using whole-genome sequence data from 2591 LBD cases and 4391 controls. We identified a significant risk locus within intron 1 of MAP3K15 (rs141773145, odds ratio = 2.42, 95% confidence interval = 1.65–3.56, p-value = 7.0 × 10−6) in female LBD cases conditioned for APOE ε4 dosage. The locus includes an enhancer region that regulates MAP3K15 expression in ganglionic eminence cells derived from primary cultured neurospheres. Rare variant burden testing showed differential enrichment of missense mutations in TEX13A in female LBD cases, that did not reach significance (p-value = 1.34 × 10−4). These findings support the sex-specific effects of genetic factors and a potential role of Alzheimer’s-related risk for females with LBD.